PENINGKATAN KINERJA PEGAWAI MELALUI PROGRAM PELATIHAN DAN ETOS KERJA DENGAN DISIPLIN KERJA SEBAGAI VARIABEL INTERVENING DI LEMBAGA PERKREDITAN DESA SE-KECAMATAN BULELENG - Kartika Ningsih, Luh; Dian Wahyuni, Kadek (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.01.TAHUN.2023DO - 10.24843/EEB.2023.v12.i01.p11, 2023)
In this study, it is intended to analyze skills development related to the role of training programs and the ethos mediated by work discipline. The author conducted a study at Village Credit Institutions in Buleleng District. The population in the study was 100 people by taking a sample of 80 LPD employees, randomly (proportional random sampling) and using the slovin formula. The measurement tool used is SEM-PLS. the analysis examines the outer model and the structural model (inner model). then testing the hypothesis along with the mediating effect. The results showed that there were 7 relationships studied, namely the effect of training programs on work discipline (0.764 < 1.96), work ethic with values ??(7.996 > 1.96) meaning, there was an influence with work discipline, there was an influence of training programs on employee performance ( 11.854 > 1.96), work ethic influences employee performance (2.158 > 1.96), there is a significant relationship between work discipline and employee performance (2.357 > 1.96), work discipline is unable to mediate training programs and employee performance (0.733 > 1.96), work discipline variables can fully mediate between work ethic and employee performance (2.131> 1.96).